Comparative Study of Banks in The Perspective of Syafruddin Prawiranegara and M. Syafii Antonio - Muhammad Amin Azis; Muhsin Hariyanto (Journal of Islamic Economic and Business Research, 2021)
The Law of Bank Interest is a complicated issue in Islamic economics because there are differences of opinion among Muslim scholars and intellectuals. This can not be separated from the observations of Indonesian Muslim economists such as Syafruddin Prawiranegara, who thinks bank interest is permissible, while M. Syafii Antonio believes bank interest is haram (forbidden in Islam). This research is entitled "Comparative Study of Banks in the Perspective of Syafruddin Prawiranegara and M. Syafii Antonio". This study aims to determine the views of Syafruddin Prawiranegara and M. Syafii Antonio regarding bank interest and examine the differences, similarities and backgrounds of their opinions. This type of research is library research with qualitative methods. The data analysis technique was carried out by means of deductive-comparative, in which this research first explains the arguments of the two figures regarding usury and bank interest then compared with the comparative method. The results of this study are 1. Syafruddin Prawiranegara believes Interest cannot be equated with usury. According to him, the difference of opinion regarding bank interest is due to a misinterpretation of the function of money. 2. M. Syafii Antonio is of the opinion that the law of bank interest is the same as usury. To stipulate the law on interest, it is necessary to comprehensively understand the stages of the derivation of the verses of usury. 3. The difference of opinion between the two is seen from the results of ijtihad (making a decision based on Islamic law) and the istinbath methods.